Air cushion barge platform for offshore wind turbine and its stability at a large range of angle. (1st December 2020) - Hao, Hongbin; Guo, Zhiqun; Ma, Qingwei; Xu, Guochun
Abstract: One of typical bases for floating offshore wind turbines is the barge platform that has merits of simpler structure and lower costs, but disadvantages of significant responses in waves. In order to improve the hydrodynamic performance of the barge platforms, in this paper a novel Air cushion Barge Platform (ACBP) is proposed, into which multiple air chambers are incorporated to mitigate the wave loads and reduce the dynamic motions due to waves. However, the existing analytical method is not suitable for evaluating the righting moment and stability of the ACBP at large angles. To address this issue, a new analytical method is developed, which can be used to quickly calculate its righting moment and evaluate its stability in the whole range of trim angles, including very large one with possible emergence of the platform bottom and so with air leakage from a few chambers before capsized. The newly proposed analytical method is calibrated by the CFD results, and then is employed for investigating the static and dynamic stability of the ACBP for two typical designs. Highlights: A novel Air-cushion Barge Platform (ACBP) was proposed for the wind turbine, which significantly enhances the stability of the system. An analytical method was developed for evaluating the stability of the ACBP in the whole range of trim angles, including large angles. The dynamic stability of the ACBP-OWT (Offshore Wind Turbine) system is investigated using the proposed method and calibrated by the stability requirement of IMO.